RUNNER COMMUNITY PERCEPTION ON SOCIABILITY, COMFORT, ACCESS, AND USAGE IN MALIOBORO PLACEMAKING (Jurnal Arsitektur ARCADE, 2026)
This study appraises the placemaking quality of the Malioboro Corridor from the perspective of the runner community, utilizing Project for Public Spaces (PPS) indicators. The Malioboro area has developed beyond its function as a commercial tourism hub to function as an active public space for recreational running. The research studies runners' perceptions of spatial quality across four variables: Sociability, Comfort & Image, Access & Linkages, and Uses & Activities. A descriptive quantitative methodology was employed, incorporating a Likert-scale questionnaire and open-ended questions, distributed to 101 purposively sampled respondents. Data analysis integrated statistical scores with qualitative responses, supported by validity (r>0.195) and reliability (Cronbach's Alpha=0.938) tests. Results show that the Sociability dimension received the highest score, demonstrating that social interaction is the primary factor animating the area. In contrast, qualitative responses reveal a physical imbalance, as runners regularly encounter "spatial negotiations" due to uneven sidewalks, crowding, and insufficient amenities. Overall, placemaking in Malioboro is currently shaped organically through social experiences and community routines, rather than by comprehensive physical infrastructure.
Keywords: Placemaking, Runner, Malioboro, Sport Tourism